Successional state of forests in the secondary moraine plains’ landscapes - N.A. Leonova (Известия высших учебных заведений. Поволжский регион: Естественные науки, 2022)
Background. Landscapes of secondary moraine plains are located to the west of the valley of the river. Sura is a low plateau of the Volga Upland. The vegetation of this area has undergone significant temporal transformation. Currently, the forest cover in the landscapes of the secondary moraine plains is no more than 13 %. Materials and methods. The biodiversity analysis was based on geobotanical descriptions obtained as a result of route and stationary studies of forest vegetation. The structural diversity of communities was assessed by the ratio of ecological-coenotic groups (ECGs) of species in the vegetation cover. To assess the successional state, we used the following parameters: representativeness of potential flora, rate of participation of R-species (explents) in the tree layer, dominance degree, proportion of demographically full-member and immoral populations. Results and conclusions. The modern vegetation cover of landscapes of secondary moraine plains is represented by 4 formations (pine, birch, aspen, black alder forests), 1 group of formations (broad-leaved forests), 10 groups of associations and 35 associations. As part of the forest flora, 196 plant species belonging to 141 genera and 59 families were identified. Phytocenoses are characterized by 43 highly constant species of exclusively nemoral ECG. All modern forests are at different stages of demutation after logging of varying degrees of intensity, grazing, fires, and plowing. Demographically complete populations are typical for a small number of shade-tolerant species of trees and shrubs. In broad-leaved forests, 70–80 % of the potentially possible number of tree species has been preserved. Demographically complete populations are typical for a small number of shade-tolerant species of trees and shrubs. In the synusia of grasses, the representation of potential flora is only 22–35 %.